Global networks : their design, engineering, and operation - Cambron, G. Keith; IEEE Xplore (Online Service); Wiley (Hoboken [New Jersey] : Wiley, 2012)
An extensive reference and a practical guide to global network design, operations and engineering practicesThe telecommunications industry has advanced in rapid, significant and unpredictable ways into the 21st century. Global Networks: Engineering, Operations and Design is an in-depth look at current and developing trends, and addresses the complex issues of designing, introducing, and managing cutting-edge communications technologies for networks of scale.The author draws upon his considerable experience in the telecommunications industry to educate engineers designing equipment and systems on the hardware and software features essential to fault tolerant operation. Design practices for network elements, management systems and IT systems are addressed in detail, and how they enable scalable engineering and operations practices. Global Networks is a complete and thorough assessment of communications networks and technologies today, written by an author of international renown.Key features:. Comprehensive treatment of the key design practices and technologies associated with the design of data, wireline and wireless networks, including equipment, systems and network design. Analysis of network outages, highlighting design and operating practices that prevent them. Written in an accessible style and fully illustrated, it offers a complete and up-to-date picture of communications technologies from initial design through to service introduction and operation. Examines future challenges such as the Exabyte traffic growth and an assessment of the dual roles of IPV4 and IPV6.
14 Disasters and Outages 297 -- 14.1 Disasters 297 -- 14.1.1 Carrier Teams 298 -- 14.1.2 Disaster Response 300 -- 14.1.3 Engineering and Design 300 -- 14.2 Outages 302 -- 14.2.1 Anatomy of an Outage 302 -- 14.2.2 Congestion Onset 307 -- 14.2.3 Congestion Propagation 307 -- 14.2.4 Root Cause 308 -- 14.2.5 Contributing Cause 309 -- 14.2.6 Triggering Events 309 -- 14.2.7 Teams in an Outage 309 -- 14.2.8 Press and External Affairs 311 -- 14.3 The Vicious Cycle 313 -- 14.3.1 Engineering and Operational Defense 314 -- 14.4 Summary 316 -- References 316 -- 15 Technologies that Matter 317 -- 15.1 Convergence or Conspiracy? 317 -- 15.1.1 Enter the World Wide Web 318 -- 15.1.2 Silicon Valley - A Silent Partner 318 -- 15.1.3 US Telecommunication Policy 318 -- 15.1.4 The Conspiracy - A Confluence of Events 319 -- 15.1.5 Local Phone Service in Jeopardy 320 -- 15.1.6 Technologies in Response 322 -- 15.2 Technologies Beyond 2012 324 -- 15.2.1 IPv6 324 -- 15.2.2 Invisible Computing 332 -- 15.2.3 Beyond 400G 334 -- 15.3 HTML5 and WEBRTC 335 -- 15.3.1 Video Evolution 337 -- 15.3.2 High Definition Voice 338 -- 15.4 Summary 340 -- References 341 -- 16 Carriers Transformed 343 -- 16.1 Historical Transformations 343 -- 16.1.1 Stored Program Control Switching 1965-1985 343 -- 16.1.2 Digital Wireline Communications 1975-2000 344 -- 16.1.3 Digital Wireless Communication 1990-Onwards 345 -- 16.2 Regulation and Investment 346 -- 16.2.1 Regulation 346 -- 16.2.2 Investment 347 -- 16.3 Consumer Wireline Networks and Services 347 -- 16.3.1 Market Trends 347 -- 16.3.2 Technology 348 -- 16.4 Wireless Networks and Services 351 -- 16.4.1 Market Trends 351 -- 16.4.2 Technology 352 -- 16.5 Backbone Networks 352 -- 16.6 Science and Technology Matter 353 -- References 353 -- Appendix A: IPv6 Technologies 355 -- Appendix B: The Next Generation Network and Why We'll Never See It 361 -- Index 367.
In Wiley online library
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/22/2015.
Keywords: Wireless communication systems; Telecommunication; Globalization; Electronic books